Grenada : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Grenada. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
Grenada made important strides under the 2014-17 ECF-supported program, achieving an impressive debt reduction by 37 percent of GDP since 2013, upgrading the framework for fiscal policy, strengthening the financial system, improving governance, and creating a better business environment. Nonetheless, public debt is still relatively high, job creation has been insufficient, and the institutional capacity for policy implementation needs strengthening.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet